The Right to Attention in The Information Economy: A Tool To Protect Individuals Against Functional Illiteracy - Nowak-Gruca, Aleksandra (Medicine, Law & Society, 2025)
In a technological reality increasingly dominated by screen devices, there has been a decline in peoples’ ability to use written and spoken language in a way that enables us to function effectively in society (functional illiteracy). Every seventh 15-year-old does not have sufficient reading skills and can only decode the text. From the perspective of education, one of the crucial causes of the threat of functional illiteracy are the significant distractions resulting from the improper use of screen devices. Thus, the modern economy, based on the exploitation of attention, appears to excessively strain individuals’ ability to concentrate, leading to a decline in cognitive autonomy and the growing problem of functional illiteracy. The aim of this article is to analyse the right to attention as a tool to protect individuals in the context of the impact of digital technologies on education and cognitive development. The article examines the relationship between the right to attention, mental integrity, educational challenges, and the necessity of regulating mechanisms within the information economy. The article highlights the particular harm that attention economy poses to vulnerable groups, especially children.